HUBUNGAN ANTARA ZINC SERUM DENGAN STATUS GIZI LANSIA - Fitrah Emawati; Sri Martuti; Joko Pambudi; Rustan Efendi (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2002)
RELATIONSHIP BETWEEN ZINC SERUM AND NUTRITIONAL STATUS OF ELDERLY PEOPLE.Background: The findings of study that 30% in Bogor and 27% in Jakarta of elderly people were undernourished. Malnutrition may occur due to infection and low food intake. Among elderly people, one of the factors that causes low food intake is affected by impairment of taste sensory and teeth function. The impairment of taste sensory is influenced by zinc status in the body.Objective: To collect food consumption pattem data of zinc rich foods, zinc concentration in serum and to analyze association of zinc concentration and nutritional status.Methods: Research design was cross sectional, and conducted in two sub districts in Bogor city. The respondents were women in 60-75 years of age, no suffering from illnesses and chronically disease. The total respondent was 90 people, and divided into three groups of 30 peoples. Data gathered included respondent identity, physical examination, anthropometry, blood biochemical and zinc dietary consumption.Results: Zinc dietary consumption adequacy of underweight group was only 30% of recommended dietary allowance, while for normal and overweight groups were 40% of dietary allowance. Zinc serum concentration of underweight group (82 ug/dl) was not significantly different with normal group (85 ug/dl), however differed significantly (p<0.05) with overweight group (95 ug/dl). Underweight group suffered 40% zinc deficiency, 27% for normal and only 7% for overweight group.Conclusions: Zinc deficiency was more prevalent in underweight group than that of normal and overweight group. [Panel Gizi Makan 2002,25: 26-33).Keywords: zinc serum concentration, zinc dietary consumption, underweight